2022
DOI: 10.3390/molecules27144543
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Role of GlcNAc6ST2 and GlcNAc6ST3 in Synthesis of CL40-Reactive Sialylated and Sulfated Glycans in the Mouse Pleural Mesothelium

Abstract: Sialyl 6-sulfo Lewis X (6-sulfo sLeX) and its derivative sialyl 6-sulfo N-acetyllactosamine (LacNAc) are sialylated and sulfated glycans of sialomucins found in the high endothelial venules (HEVs) of secondary lymphoid organs. A component of 6-sulfo sLeX present in the core 1-extended O-linked glycans detected by the MECA-79 antibody was previously shown to exist in the lymphoid aggregate vasculature and bronchial mucosa of allergic and asthmatic lungs. The components of 6-sulfo sLeX in pulmonary tissues under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 65 publications
(98 reference statements)
2
11
0
Order By: Relevance
“…Unexpectedly, mice deficient in GlcNAc6ST2 showed negligible levels of pleural R-10G signals ( Figure 3 A,B). As seen in the previous report [ 3 ], the mesothelin-positive mesothelium was thickened in GlcNAc6ST2 KO and GlcNAc6ST3 KO mice ( Figure 3 A). R-10G signals in these KO mice were not colocalized with laminins ( Supplementary Materials Figure S2 ).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Unexpectedly, mice deficient in GlcNAc6ST2 showed negligible levels of pleural R-10G signals ( Figure 3 A,B). As seen in the previous report [ 3 ], the mesothelin-positive mesothelium was thickened in GlcNAc6ST2 KO and GlcNAc6ST3 KO mice ( Figure 3 A). R-10G signals in these KO mice were not colocalized with laminins ( Supplementary Materials Figure S2 ).…”
Section: Resultssupporting
confidence: 87%
“…We previously showed that the 6-sulfo sLe X present in the high endothelial venule (HEV) cells of peripheral lymph nodes is complementarily synthesized by GlcNAc6ST1 and GlcNAc6ST2 [ 15 , 16 ]. Recently, we reported that GlcNAc6ST2 and GlcNAc6ST3 are complementary to the synthesis of sialyl 6-sulfo LacNAc recognized by CL40 in the mouse pleura [ 3 ]. We wished to determine which GlcNAc6ST is responsible for the synthesis of R10G-reactive glycans in the mouse pleural mesothelium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations